Organic pollution level and water quality in Poso river with macroinvertebrate indicators - Indri Novayanti Gala; Shelvy Ferawati Rurua (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2022)
The Poso river is one of the rivers in the Poso Regency that is utilized as a water source and channeled to people's homes by the Regional Drinking Water Company. There are also people who take water directly from the river for consumption. However, there is a lot of garbage/waste found on the banks and bodies of the river due to the economic and social activities of the people living along the Poso river. There are several home industries that dispose of their industrial waste directly into the Poso river, causing pollution that affects the water quality of the Poso river. The objective of this study was to analyze the level of organic pollution and water quality in the Poso river with macroinvertebrates as biological indicators. The research samples were all macroinvertebrates found at the time of sampling at each station. Data collection/sampling was conducted at four stations, namely station 1 in residential areas; station 2 at the central market and industrial activity; station 3 in the tofu factory; and station 4 in the estuary area. Data was collected by determining the point for sampling first. The bottom substrate of the Poso river was mud so that macroinvertebrates could only be collected by sweeping techniques. The data analysis technique used was the FBI (Family Biotic Index) formula. The results showed that there were 10 taxa of macroinvertebrate biota families obtained at all research stations with a Family Biotic Index (FBI) value of 6.13. This means that the water quality of the Poso river in the Poso Kota Selatan and Poso Kota Sub-districts is rather poor.